LnUO4‐based glass–ceramic composites as waste forms for the immobilization of lanthanide‐bearing uranium wastes. Issue 12 (29th July 2022) - Lu, Kimbal T.; Zhang, Yingjie; Wei, Tao; Murphy, Gabriel L.; Bhuiyan, Aurpa; Scales, Nicholas; Zheng, Rongkun
Abstract: We report a comprehensive study on lanthanide monouranate–based glass–ceramic (GC) composites as potential waste forms for the immobilization of the lanthanide actinide fraction waste arising from the reprocessing of spent nuclear fuel (SNF). Although the crystalline LnUO4 precursor prepared via a nitrate route can be well stabilized in a sodium aluminoborosilicate glass, the in situ crystallization of EuUO4 in glass from oxide precursors (Eu2 O3 and U3 O8 ) is rather robust with regards to various processing conditions such as waste loadings, ceramic‐to‐glass ratios, and cooling rates. Scanning electron microscopy and transmission electron microscopy investigations revealed the detailed microstructures, where ∼1–5‐μm spheres for NdUO4 and EuUO4, and ∼1–5‐μm rectangular crystals for DyUO4 and HoUO4 were observed in residual glasses. As designed, the pentavalent uranium has been confirmed by diffuse reflectance spectroscopy. Overall, LnUO4 ‐based GC composite waste forms are chemically durable, offering flexible processing options with wide operating windows for SNF and process waste stream management. Abstract :